2017
DOI: 10.1186/s13000-017-0609-4
|View full text |Cite|
|
Sign up to set email alerts
|

Cytokeratin7 and cytokeratin19 expression in high grade cervical intraepithelial neoplasm and squamous cell carcinoma and their possible association in cervical carcinogenesis

Abstract: BackgroundHigh risk human papillomavirus (HR HPV) infects cells at the squamocolumnar junction (SCJ) of the cervix, causing cancer. Cytokeratin (CK)7 is an SCJ marker, and stains cervical neoplasia. CK19 is a binding partner of CK7 and expressed in cervical cancer. Despite this possible association between CK7/CK19 and cervical cancer, not much is known about the mechanism of CK7/CK19 involvement in HR HPV-mediated cervical carcinogenesis.MethodsWe analyzed the expression pattern of CK7, CK19, and p16 by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Previously, the majority of studies investigated the prognostic or diagnostic significance of individual CK7 or CK19 in various kinds of cancers, with the ignorance of combined CK7 and CK19. Recently, Lee et al reported that CK7 was a binding partner of CK19 in cervical cancer, and both were involved in HPV‐mediated cervical carcinogenesis. Although CK7 and CK19 mainly expressed in the bile duct epitheliums, several studies also asserted that CK7 and CK19 could be expressed in HCC and affecting prognosis of HCC patients .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the majority of studies investigated the prognostic or diagnostic significance of individual CK7 or CK19 in various kinds of cancers, with the ignorance of combined CK7 and CK19. Recently, Lee et al reported that CK7 was a binding partner of CK19 in cervical cancer, and both were involved in HPV‐mediated cervical carcinogenesis. Although CK7 and CK19 mainly expressed in the bile duct epitheliums, several studies also asserted that CK7 and CK19 could be expressed in HCC and affecting prognosis of HCC patients .…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillar and uterine cervical SCCs share some histopathological and immunohistochemical features. They both arise in CK7 and CK19 positive squamocolumnar junctional cells infected by HR HPV and frequently accompany intratumoral cystic changes . In an earlier study, we observed cystic change in a subset of uterine cervical SCC and topological differences between the expressions of CK7, CK19, and p16 .…”
Section: Discussionmentioning
confidence: 58%
“…They both arise in CK7 and CK19 positive squamocolumnar junctional cells infected by HR HPV and frequently accompany intratumoral cystic changes. 4,5,7,9 In an earlier study, we observed cystic change in a subset of uterine cervical SCC and topological differences between the expressions of CK7, CK19, and p16. 9 The present case exhibited a staining pattern similar to that of uterine cervical SCC, that is, patchy CK7 staining in the inner portions of cystic tumor nests, diffuse CK19 staining in cystic and solid tumor nests, and strong p16 staining in solid tumor component.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition to being actively involved in adult adaptive processes (metaplasia, hyperplasia) [10], SC junction cells exhibit intriguing phenotypic similarities with approximately 90% of cervical SCC and high-grade precursors [9,12]. These findings underlying the instrumental role of junctional cells in cervical carcinogenesis were recently confirmed by several immunohistochemical and/or transcriptional studies analyzing the expression of SC junction-overexpressed biomarkers (i.e., cytokeratin 7 (Krt7), anterior gradient protein 2 (AGR2) or cystic fibrosis transmembrane conductance regulator (CFTR)) in large cohorts of cervical (pre)neoplastic lesions [13,14,15,16,17]. Moreover, the evidence that normal-appearing SC junction cells harbor both HPV transcripts (E6*I/II) and early viral proteins (HPV E2) was reported and sustains the possibility that these cuboidal cells could serve as a reservoir for latent infections and subsequent CIN development in asymptomatic HPV-positive patients [18].…”
Section: Introductionmentioning
confidence: 93%